PRIORITIES OF PUBLIC ADMINISTRATION IMPROVEMENT IN CIVIL PROTECTION OF TERRITORIAL COMMUNITIES UNDER POWER DECENTRALIZATION IN UKRAINE - Kostenko V.O. (Pressing Problems of Public Administration, 2017)
The paper considers the priority directions of public administration improvement in the  eld of civilprotection at the level of associated territorial communities in the process of implementing the localgovernment reform and territorial organization of power in Ukraine. The main tasks of the StateEmergency Service of Ukraine in providing assistance to local government bodies in their organizationof civil protection measures aimed to ensure a reliable protection of the population and territories fromtechnogenic and natural emergencies are analyzed.